Functions starlike with respect to other points - Abdul Halim, S. (Hindawi Publishing Corporation, 1991)
In [7], Sakaguchi introduce the class of functions starlike with respect to symmetric points. We extend this class. For p≤β<1, let SS*(β) be the class of normalised analytic functions f defined in the open unit disc D such that Rezf′(z)/(f(z)−f(−z))>β, for some z ϵ D. In this paper, we introduce 2 other similar classes SC*(β), SSC*(β) as well as give sharp results for the real part of some function for f ϵ SS*(β), SC*(β) and SSC*(β) The behaviour of certain integral operators are also considered.